2022
DOI: 10.1136/rmdopen-2021-002058
|View full text |Cite
|
Sign up to set email alerts
|

Association between social deprivation and disease activity in rheumatoid arthritis: a systematic literature review

Abstract: Physical and mental illnesses are driven by ethnicity, social, environmental and economic determinants. Novel theoretical frameworks in rheumatoid arthritis (RA) focus on links and adverse interactions between and within biological and social factors. This review aimed to summarise associations between socioeconomic status (SES) and RA disease activity, and implications for future research. Articles studying the association between SES and RA disease activity were identified, from 1946 until March 2021. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Although several studies have described D2T RA-related factors in patients with RA17 30 31 with long-standing disease, the effect of different variables on this outcome has not been studied in the early stages of disease, and comparisons between them would not be accurate. In addition, consideration should be given to the possibility of other lifestyle, economics and non-modifiable sociodemographic factors that may contribute to the development of D2T RA 14 32–35…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have described D2T RA-related factors in patients with RA17 30 31 with long-standing disease, the effect of different variables on this outcome has not been studied in the early stages of disease, and comparisons between them would not be accurate. In addition, consideration should be given to the possibility of other lifestyle, economics and non-modifiable sociodemographic factors that may contribute to the development of D2T RA 14 32–35…”
Section: Discussionmentioning
confidence: 99%
“…These studies have concluded that social isolation can lead to worsening of neuropsychiatric symptoms and motor function,35 36 although these effects are not restricted to PD 37. Evidence for the influence of social exclusion on health outcomes comes from other studies of chronic conditions, such as dementia,38 diabetes,39 HIV40 and rheumatoid arthritis 41…”
Section: Discussionmentioning
confidence: 99%
“…For instance, investigations into cardiovascular disease49 50 have revealed how socioeconomic disparities can affect disease risk. Similarly, studies on rheumatoid arthritis51 have shed light on the interplay between socioeconomic status and deprivation and disease outcomes. Furthermore, a study of patients with chronic kidney disease52 has shown how deprivation can contribute to the burden of renal diseases.…”
Section: Discussionmentioning
confidence: 99%